Keharmonisan Keluarga, Konsep Diri dan Kenakalan Remaja - Muniriyanto, Muniriyanto; Suharnan, Suharnan (Persona:Jurnal Psikologi Indonesia, 2014)
Abstract. The research was aimed to find out the relation of family harmony and self-concept  with adolescent’s delinquency.  The subjects were students from MA Mambaul Ulum in Al-Khairat Foundation and SMK Mambaul Ulum in Mambaul Ulum Foundation, East Java. 162 students completed the questionnaires.Multistage Cluster Sampling by random technique with the characteristic subject was used to determine the sample of the research. The characteristics of the research  subject were: (1) the ages of fourteen and eightteen years-old, (2) living with both of their parents, (3) male or female, (4) not a single child. The instrumens were scale of tendency of adolescent’s delinquency, scale of family harmony, and self-concept scale. The responses of questionnaires used 4- likert point. Data analysis method used in this research was regression analysis. Hypothesis shows that family harmony and self-concept gave contribution to the tendency of adolescent’s delinquency. the result of hypothesis showed that the Family harmony and self concept give a role of adolescent’s delequency tendency. Based on the value of stepwise regression by Multistage Cluster Sampling technic to the data of adolescent’s delequency with family harmony and self-concept found a value of coefficient correlation F-reg = 6,720, p 0,000 < 0,05 and coefficient determinant R2 = 0.152 or 15,2 %. The result was significant so that the hypothesis was accepted. The conclusion is there was the relation of family harmony and self-concept with adolescent ’s delinquency. Keywords : family harmony, self-concept, and adolescent’s Delinquency